Cochlear implants in children younger than 6 months - Colletti, Liliana; Mandalà, Marco; Colletti, Vittorio (Otolaryngology-head and neck surgery, 2012)
(1) To determine the long-term outcomes of cochlear implantation in children implanted younger than 6 months and (2) to evaluate auditory-based performance in very young children compared with older children, all with profound sensorineural bilateral hearing loss. Prospective cohort study. Tertiary referral center. Twelve subjects aged 2 to 6 months, 9 aged 7 to 12 months, 11 aged 13 to 18 months, and 13 aged 19 to 24 months, all with profound bilateral hearing loss, were fitted with cochlear implants and followed longitudinally for 4 years. Subjects were developmentally normal with no additional disabilities (visual, motor, or cognitive). Auditory-based communication outcomes included tests for speech perception, receptive language development, receptive vocabulary, and speech production. Age at cochlear implantation was a significant factor in most outcome measures, contributing significantly to speech perception, speech production, and language outcomes. There were no major complications and no significantly higher rates of minor complications in the younger children. This article reports an uncontrolled observational study on a small group of infants fitted with cochlear implants following personal audiological criteria and, up to now, with limited literature support due to the innovative nature of the study. This study shows, for the first time, significantly improved auditory-based outcomes in children implanted younger than 6 months and without an increased rate of complications. The data from the present study must be considered as explorative, and a more extensive study is required.